Creating a Participatory Planning Approach Based on Swedish Visual Preferences for Building and Urban Design - Karim Najar; Ola Nylander; William Woxnerud (Advances in Civil Engineering)
This research aims to foster social sustainability by allowing residents to participate in community decisions and creating a sense of belonging. Utilizing the photoelicitation technique, we conducted a visual preference survey with an average of 457 participants in Sweden to assess the physical and urban features of local development projects. The composite assessment of built environment quality was based on 11 qualities: urban planning, building mass configurations, building orientation, parking planning, roof articulation, building materials, color scheme, entrance articulation, fenestration, and balcony articulation and placement. We conducted a subjective qualitative analysis and quantitative evaluation of the photoelicitation data. The study identified the most preferable features leading to the highest rankings, presented a novel method to increase the participatory process’s efficacy, and developed an assessment matrix based on the quality ranking of the 12 features. The primary outcome was the development of methods for knowledge transfer and quality assessment of built projects in Nordic cities, with a focus on putting residents’ voices front and center in urban development.